AGRARIAN LAND MANAGEMENT DYNAMICS AND CROP PRODUCTION: INSIGHTS FROM THE BUI HIGHLANDS OF CAMEROON - Mbuh, Bailack; Paul Tume , Suiven John; Cheenuwenui Boeyeo , Akuo (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
The land is an integral identity and the ultimate prerequisite for human survival. It constitutes the agro-resource base with inherent inequalities in the distribution of cropland potentials. The Bui Highlands of Cameroon is a citadel of agrarian resources, with edgy perceptions of ownership entitlements to satisfy land-hungry anxieties on the agrarian landscapes. This study, therefore, aims to examine the impact of agrarian land management on crop production. A survey and comparative research designs were used to obtain primary and secondary data. Questionnaires, interviews, and focus group discussions from 16.9% of the farming population in 504 households were used. Findings revealed that cropland is a major agrarian resource, with inequalities in the distribution and diverse management practices linked to high cropping systems. Cropping indices range from 100-300, with 72% of the population already involved in innovative modern agricultural practices as 90% of households are food secured. Staple crop production anomalies are attributed to climatic shocks and other environmental stressors affecting land-based resources. This indicates a significant increase in the trends of agrarian land management for cropland sustainability, with positive livelihood patterns linked to food security. This calls for the need to improve cropland management security at the grassroots level to safeguard the inextricable link between agrarian resource management and livelihood sustenance in highlands areas.